Caracterización de las instituciones educativas- distrito 13D07 en relación a la implementación del plan institucional de continuidad educativa, Manabí, período 2020-2021 - Andrade Cedeño, Lisseth Stefania (2022)
The Institutional Plan for Educational Continuity (PICES) was implemented to prevent student desertion in the face of the COVID-19 pandemic in District 13D07, Chone-Flavio Alfaro canton, Manabí province. The objective was to evaluate the implementation of the PICES for the period 2020/2021 in District13D07. The PICE matrix filled out by 386 educational institutions that make up District 13D07 and 50 variables was evaluated. The following results were obtained: The inadequate filling of the PICE of District 13D07 Chone-Flavio Alfaro cantons does not allow the analysis of 23.1% of the Educational Institutions, which goes against the Public Policy Management. Of the 297 educational institutions, there was a student desertion rate of 8.42%. This shows the effectiveness of the PICE to stop student desertion. The highest desertion of 4.27% was observed in institutions where: 83.5% of the educational institutions were rural (247 educational institutions) and 11 urbans, all of them of fiscal regency. The school day was morning (98.78%). The total number of students was 6,317 and 499 teachers. Most of them were high school-elementary-middle school (82.99%). 100% registered PICE in the application. 1.16% of students submitted a return plan. The total number of students contacted with connectivity (also considering the connection via whatsapp) was 50.36%. The total number of connected students was 98.44%. The total number of students contacted without connectivity was 48.09%. The total number of students not contacted (no communication could be established since the beginning of classes) was 5.38%. 12.95% carried out personalized accompaniment activities through home visits and classroom attendance.